The effect of nutrition and reproductive health education of pregnant women in Indonesia using quasi experimental study - Tria Astika Endah Permatasari; Fauza Rizqiya; Walliyana Kusumaningati; Inne Indraaryani Suryaalamsah; Zahrofa Hermiwahyoeni (BMC, 2021)
Abstract Background Almost one-third of children under 5 years old in Indonesia suffer from stunting. Stunting can be prevented optimally during pregnancy as the initial phase of the first 1000 days of life. This study aims to determine the effect of nutrition and reproductive health education of pregnant women in Bogor Regency, Indonesia. Methods A quasi-experimental study was conducted among 194 pregnant women from August to November 2019. The pregnant women were randomly selected from four different villages in Bogor Regency. The intervention group (n = 97) received 2 h of nutrition and reproductive health education in small groups (four or five mothers per group) every 2 weeks for 3 consecutive months. This interactive education was given by facilitators using techniques such as lectures, role-playing, simulation, and games. The control group (n = 97) received regular health care services. A structured questionnaire was applied to collect data consisting of maternal characteristics, nutritional and reproductive health knowledge, attitudes, and practices in the intervention and control groups. Data were analysed using t-test and chi-square analysis. Results Pregnant women in the intervention group indicated a significant increase in knowledge, attitudes, and practices regarding nutrition and reproductive health after receiving education. The pre-test and post-test mean scores in the intervention group were 55.1 and 83.1 for overall knowledge, 40.2 and 49.0 for attitudes, and 36.2 and 40.2 for practices, respectively. In the control group, there was no significant difference between the pre-test and post-test mean scores for these three variables. There was a significant difference (P < 0.001) in the post-test mean between the intervention group and the control group, but the difference was not significant (P > 0.05) in the pre-test. Conclusion Providing nutrition and reproductive health education through small groups with interactive methods improves the knowledge, attitudes, and practices of pregnant women. This intervention has the potential to be replicated and developed for large-scale implementation by optimising collaboration between government, non-governmental organizations, and maternal and child health service providers.